2006
DOI: 10.1086/506140
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of NGC 2264: Signs of Cluster Formation

Abstract: We present results from 1078 high resolution spectra of 990 stars in the young open cluster NGC 2264, obtained with the Hectochelle multiobject echelle spectrograph on the 6.5m MMT. We confirm 471 stars as members, based on their radial velocity and/or Hα emission. The radial velocity distribution of cluster members is non-Gaussian with a dispersion of σ ≈ 3.5km s −1 . We find a substantial north-south velocity gradient and spatially coherent structure in the radial velocity distribution, similar to that seen … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
138
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(155 citation statements)
references
References 38 publications
17
138
0
Order By: Relevance
“…explosion about 6-7 Myr ago was suspected as the source of the external trigger. The presence of the subclusters can also be found in the velocity field obtained from 13 CO observations and stellar radial velocity survey (Fűrész et al 2006;Tobin et al 2015). The radial velocity distribution of the cluster members shows a velocity gradient of 10 km s −1 along the north-south direction.…”
Section: Age Spread and Cluster Formation Timescalementioning
confidence: 68%
See 2 more Smart Citations
“…explosion about 6-7 Myr ago was suspected as the source of the external trigger. The presence of the subclusters can also be found in the velocity field obtained from 13 CO observations and stellar radial velocity survey (Fűrész et al 2006;Tobin et al 2015). The radial velocity distribution of the cluster members shows a velocity gradient of 10 km s −1 along the north-south direction.…”
Section: Age Spread and Cluster Formation Timescalementioning
confidence: 68%
“…The star shows a weak Hα absorption line and broad metallic lines. Fűrész et al (2006) identified the star as a spectroscopic binary from their multi-epoch spectroscopic observations. The star is brighter than other stars at a given color in Figure 10.…”
Section: Discussion On the Li-deficient Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand this evolution we also need to study what is happening in the kinematic subspace during this evolution. There have already been a number of detections of kinematic substructure (e.g., Fűrész et al, 2006;Jeffries et al, 2014, see Figure 7), suggesting it might be a very common phenomenon in young star forming structures. Emilio explained how this kinematic substructure can be detected and measured using the minimum spanning tree, an algorithm that has already been effective in diagnosing spatial substructure (Cartwright & Whitworth, 2004).…”
Section: The Kinematics Of Young Stars In Star Clusters and Ob Associmentioning
confidence: 94%
“…(Hénault-Brunet et al, 2012) and kinematic substructure (Fűrész et al, 2006;Jeffries et al, 2014, see Figure 7). Proper motions and radial velocities can also be used to measure kinematic parallaxes, which Galli et al (2013) used to reveal significant depth effects between the different subgroups of the Lupus associations, showing that the (likely older) weak-lined T-Tauri stars are more dispersed in both angular extent and depth compared to the (younger) Classical T-Tauri stars.…”
Section: The Kinematics Of Young Stars In Star Clusters and Ob Associmentioning
confidence: 96%